PENDUGAAN KARBON TERSIMPAN DI HUTAN MANGROVE DESA BLONGKO KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN - Andreas A. TH. Suli; Johny S. Tasirin; Fabiola B. Saroinsong; Maria Y.M.A. Sumakud (Universitas Sam Ratulangi, 2015)
ABSTRACT Â The purpose of this research is to estimate the amount of carbon stored in the biomass of mangrove forests in Blongko Village, District Sinonsayang, South Minahasa regency.The study was conducted over two months, from July to September 2014. This research method used 15 sampling plots 20x20 m2 each. Data Analysis used allometric equations to obtain the biomass of each species. Carbon store was assumed to be 0.47 factors of total biomass. The result showed that total carbon store and biomass were 17914.59 Mg and 8419.86 Mg with an average of 409.5 Mg ha-1Â and 192.5 Mg ha-1 respectively.Â Keywords: Carbon store, Biomass, Mangrove, Blongko Village, South Minahasa Regency.